The Influence of the Financial and Banking Sector on the Development on the Tourism Industry in the Context of the Crisis of the Global Economic System - SULTANBAIULY, Serik; NASYRHANOV, Arsen; KHAN, Yury; KENENOVA, Karlygash; KONUSPAYEV, Ruslan; BAZARBAYEV, Assylbek (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).16, 2022)
The article discusses how the conditions and influence of the financial system, including the banking sector, on the development of tourism in the conditions of the crisis of the global economic system are changing. A modern analysis of the state of the banking sector, indicators of assets and liabilities of second-tier banks, and the share of tourism in the formation of GDP has been carried out. Assessment of the current state of the credit activity of commercial banks in Kazakhstan, economic and mathematical forecast of its further development, development of proposals to improve the efficiency of the bank's financial management and substantiation of merits. Recommendations are given to improve the financial efficiency of the bank's management activities and the main directions of stabilization measures. It is noted that investments are a tool for financial stabilization of the economy, play a huge role in solving strategic and tactical tasks at the strategic level. All this should lead to financial stabilization of the economy, reduction of inflation, unemployment and economic growth.